Psychosocial Analysis of Familicide Offenders: A Forensic Psychology Perspective in Indonesia - Tsabita Zulfihandari; Dharma Alkautsar Mahadika (LifeSciFi, 2026)
Familicide represents a complex form of interpersonal violence that cannot be adequately explained solely through psychopathological or legal approaches. This study examines familicide in Indonesia through an integrated psychosocial and forensic psychology perspective. The study aims to analyze the interaction between psychological vulnerabilities and socio-structural factors that contribute to violent behavior within family relationships. A qualitative design using a Systematic Literature Review (SLR) approach was employed by synthesizing findings from Indonesian and international scholarly sources related to familicide, forensic psychology, and psychosocial criminology. The findings indicate that familicide is shaped by the accumulation of multiple risk factors, including emotional dysregulation, impulsivity, low self-control, economic hardship, family conflict, dysfunctional family dynamics, and limited social support. These factors interact over time and increase the likelihood of violence within the domestic environment. The review further highlights the role of forensic psychology as an integrative framework that connects psychological assessment with broader social and environmental influences in understanding offender behavior. The study concludes that familicide should be viewed as a multidimensional phenomenon requiring comprehensive assessment and intervention. The findings imply the need for culturally sensitive forensic assessment protocols, early prevention strategies, multidisciplinary collaboration, and community-based support systems to strengthen familicide prevention and intervention efforts in Indonesia.